Comparative Transcriptomics Reveals Differential Gene Expression Related to Colletotrichum gloeosporioides Resistance in the Octoploid Strawberry - Wang, Feng; Zhang, Feng; Chen, Mengmeng; Liu, Zhiheng; Zhang, Zhihong; Fu, Junfan; Ma, Yue (Frontiers in Plant Science, 2017)
The strawberry is an important fruit worldwide. The development of the strawberry industry is limited by fungal disease. Anthracnose is caused by the pathogen Colletotrichum gloeosporioides and leads to large-scale strawberry losses in terms of quality and production. Different strawberry cultivars have different response to this pathogen. However, the genetic mechanisms underlying this difference and the transcriptional response of strawberry to infection with C. gloeosporioides is poorly understood. In the present study, the strawberry leaf transcriptome of the ‘Yanli’ and ‘Benihoppe’ cultivars were deep sequenced via an RNA-seq analysis to study C. gloeosporioides resistance in strawberry. Among the sequences, differentially expressed genes (DEGs) were annotated with Gene Ontology terms and subjected to pathways enrichment analysises, the significant categories included defense, plant-pathogen interactions and flavonoid biosynthesis. The comprehensive transcriptome data set unprecedented molecular insight into C. gloeosporioides resistance genes between Resistance and Susceptibility strawberry cultivars. They were validated for the impact of breeding in strawberry.